Pneumolabyrinth following cochlear implantation resolved after shunt adjustment. Issue 1 (1st January 2020) - Hallin, Karin; Stillesjö, Fredrik; Sundblom, Jimmy; Danckwardt-Lillieström, Niklas
Abstract: We present a case of a male with a history of repeated surgeries for a cerebellar astrocytoma, leading to profound deafness and facial paresis on the left side. A ventriculoperitoneal (VP) shunt was inserted to manage hydrocephalus. At the age of 46 the hearing suddenly disappeared on the right side, where he received a cochlear implant (CI). At implant activation, impedances showed atypical high values. One month later impedance levels had further increased and the patient had no benefit from the CI. A computed tomography (CT) scan suggested air in the cochlea (pneumolabyrinth). The shunt was adjusted to elevate the cerebrospinal fluid (CSF) pressure and the pressure in the perilymph to prevent air from entering the cochlea via the round window. One year after activation the electrode impedances were normal and the hearing outcome from the implant was successful.